Hubungan penerapan sistem akuntansi keuangan terhadap kualitas laporan keuanganpada dinas pengelolaan keuangan dan asset daerah kota bukittinggi - Rahmadani, Kiki; Adriansyah, Adriansyah (JURNAL PUNDI, 2018)
AbstractBukittinggi city in financial reports in a few years ago still not meet the criteria of the value of the required information visible gain from the opinions of Local Government Financial Report Bukittinggi city. One of the guidance in the assessment of a financial report of the compliance to the regulation and the presentation of the financial report with the criteria that have been assigned. The purpose of this research is to know the influence of the implementation of regional financial accounting system to the quality of the Regional Financial Report on DPKAD Bukittinggi city. Announcement of samples in this research are using Slovin method by as much as 77 respondents. Analysis methods used namely Rank Spearmen Correlation analysis. The findings of this research shows that the implementation of regional financial accounting system have positive and significant impact on the quality of the Regional Financial Report on DPKAD Bukittinggi city. This can be seen from the results of the assessment of the respondents against the implementation of regional financial accounting system reached 95%. While the quality of the Regional Financial Report produced DPKAD Bukittinggi city is very good with the level of the assessment respondents reached 90%. As well as the significant value by using Correlation Coefficient analysis Rank Spearmen reach 0,564.Key Words: financial accounting system (earlier), the quality of Financial Report